Minimum 10-Year Outcomes After Revision Anatomic Coracoclavicular Ligament Reconstruction for Acromioclavicular Joint Instability. Issue 9 (16th September 2020) - Berthold, Daniel P.; Muench, Lukas N.; Beitzel, Knut; Archambault, Simon; Jerliu, Aulon; Cote, Mark P.; Scheiderer, Bastian; Imhoff, Andreas. B.; Arciero, Robert A.; Mazzocca, Augustus D.
Background: Revision surgery in cases of previously failed primary acromioclavicular (AC) joint stabilization remains challenging mainly because of anatomic alterations or technical difficulties. However, anatomic coracoclavicular ligament reconstruction (ACCR) has been shown to achieve encouraging biomechanical, clinical, and radiographic short-term to midterm results. Purpose: To evaluate the clinical and radiographic long-term outcomes of patients undergoing revision ACCR after failed operative treatment for type III through V AC joint injuries with a minimum 10-year follow-up. Study Design: Case series; Level of evidence, 4. Methods: A retrospective chart review was performed on prospectively collected data within an institutional shoulder registry. Patients who underwent revision ACCR for type III through V AC joint injuries between January 2003 and December 2009 were analyzed. Clinical outcome measures included the American Shoulder and Elbow Surgeons (ASES) score, Simple Shoulder Test (SST), and Single Assessment Numeric Evaluation (SANE). The coracoclavicular distance (CCD) was measured for radiographic analysis immediately postoperatively and at last postoperative follow-up. Results: A total of 8 patients with a mean age at the time of surgery of 44.6 ± 10.6 years and a mean follow-up of 135.0 ± 17.4 months (range, 120-167 months) were eligible for inclusion in the study. The time from initial AC joint stabilization until revision surgery was 10.2 ± 12.4 months (range, 0.5-36 months); 62.5% of the patients had undergone more than 2 previous AC joint surgical procedures. The ASES score improved from 43.9 ± 22.4 preoperatively to 80.6 ± 28.8 postoperatively ( P = .012), the SST score improved from 4.4 ± 3.6 preoperatively to 11.0 ± 2.2 postoperatively ( P = .017), and the SANE score improved from 31.4 ± 27.3 preoperatively to 86.9 ± 24.1 postoperatively ( P = .018) at final follow-up. There was no significant difference in the CCD ( P = .08) between the first (7.6 ± 3.0 mm) and final (10.6 ± 2.8 mm) radiographic follow-up (mean, 50.5 ± 32.7 months [range, 18-98 months]). Conclusion: Patients undergoing revision ACCR after failed operative treatment for type III through V AC joint injuries maintained significant improvement in clinical outcomes at a minimum 10-year follow-up.